Еdgе fiеld of dеflеctorplаtes with expanding screens - Spivak-Lavrov, I.F.; Sharipov, S.U.; Seiten, A.B.; Trubitsyn, A.A. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2024)
Deflector plates consist of two parallel conductive plates that create a deflecting electric field. They can be used to control the flow of charged particles ― electrons or ions. The effect of the еdgе fiеld of deflector plates leads to a change in the velocity of charged particles in the longitudinal and transverse directions, consequently of which their real trajectories change, deviating from ideal ones, which violates the space-time resolution of corpuscular optical devices in which they are used. Apart from that, the electric field at the input to the plates of deflector can vary over time, which must also be taken into account when the deflector diverts the beam of charged particles. Thus, in many cases, the use of deflector plates with open ends is inappropriate, since uncontrolled scattering fields are formed. In this article, we can consider the field of deflector plates with expanded screens at the output, so that deflecting beams of charged particles can be used at the output of deflector plates. Using the methods of the theory of complex variable functions, analytical expressions for the edge field of deflector plates with grounded screens were obtained. Firstly, by grounding the screens and shielding the plates from the deflection field, we can localize the edge electric field and reduce the uncontrolled scattering fields, and secondly, such a field can be accurately calculated analytically.
Кеңейтілген экрандары бар дефлекторлық пластиналардың шеткі өрісі
Краевое поле дефлекторных пластин с расширяющимися экранами
Keywords: deflector plates; grounded screens; edge field; boundary problem of electrostatics; electron beam control